Effect of Raltitrexed on ECA109 Cellular Radiosensitivity and its Mechanism in Esophageal Cancer - Xu, Li-Ben; Wu, Chao-Yang; Wang, Yan; Zhou, Ju-Ying (Current Pharmaceutical Design, 2024)
Background: To investigate the effect of raltitrexed + X-ray irradiation on esophageal cancer ECA109 cells and analyze the potential action mechanism. Methods: The 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay was used to analyze the inhibitory effect of raltitrexed on cell proliferation. The effect of raltitrexed on radiosensitivity was studied through a clone-forming experiment. The scratch assay and invasion test were performed to understand the cell migration and invasion abilities. The apoptosis rate change was measured using a flow cytometer, and Western Blotting was used to determine the expression of B cell lymphoma-2 (Bcl-2) and Bcl2-associated X protein (Bax) in each group. Results: Raltitrexed significantly inhibited ECA109 proliferation in a time-dose-dependent manner; there were significant differences among different concentrations and times of action. The results of the clone-forming experiment showed a sensitization enhancement ratio of 1.65, and this demonstrated a radiosensitization effect. After the combination of raltitrexed with X-ray, the cell migration distance was shortened, and the number of cells penetrating the membrane was reduced. Conclusion: Raltitrexed can inhibit the growth of esophageal cancer ECA109 cells and has a radiosensitization effect.
Keywords: Raltitrexed